Difluoroboron Curcumin Complex: A Study on Determination of Acidity Constants and Quantitative Analysis of Arsenic(III) - Nguyen Quoc Thang; Tran Nguyen Minh An; Le Thi Thanh Tran; Do Tam Nhan; Mai Ngoc Tan; Le Van Tan (Universitas Gadjah Mada, 2021)
In this study, the complex of difluoroboron, curcumin (BF2-Cur), has been synthesized and characterized via the combination of Boron trifluoride-diethyl etherate ((C2H5)2OBF3) and curcumin. However, the new dissociation constants, pKa1 and pKa2 of the BF2-Cur complex, have been indicted by the values of 8.44 ± 0.16 and 9.76 ± 0.13, respectively. On the other hand, the reagent was also used to determine As(III) in aqueous solutions by UV–Vis spectrophotometry. As a result, the method was validated for accuracy, precision, linearity, and sensitivity, and the linear range was from 1.0 to 25.0 µmol/L, with the linear regression, A = 0.0027 C + 0.0106, correlation coefficient R2 = 0.9969. Besides, the limit of detection (LOD) and limit of quantification (LOQ) were determined as 0.83 and 2.10 µmol/L, respectively. Thus, the developed method is successfully used for quantitative analysis of total arsenic in wastewater by reducing As(V) to As(III), then determining As(III) with high accuracy results.